Morphological analysis of the cellular interactions between the eugregarine Gregarina garnhami (Apicomplexa) and the epithelium of its host, the desert locust Schistocerca gregaria - Valigurová, Andrea; Koudela, Bretislav (European journal of protistology, 2008)
Morphological features of the eugregarine Gregarina garnhami (Canning, 1956) parasitic in the caeca and mid-gut of the desert locust, Schistocerca gregaria, have been studied by transmission and scanning electron microscopy, with particular attention to the epimerite and the relationship between the epimerite and the host epithelium. The cytoplasmic core of the globular epimerite is overlain by a distinct cortical zone, limited on its cytoplasmic face by a membrane-like structure, with an underlying layer of mitochondria. The periphery of the cortical zone is strengthened by a mass of fine filaments, especially at its base. Fine tubular structures, apparently arising from the membrane-like structure, pass through the cortical zone and attach to the epimerite-host cell interface. The base of the cortical zone is supported by a distinct osmiophilic ring. The epimerite is separated from the rest of the gregarine body by a discontinuous septum. Maturing and mature trophozoites possess conically arranged fibrils, which arise from the epimeritic septum and continue into the protomerite region. The epimerite and associated structures are here discussed with regard to the detachment of the trophozoite from the host epithelium. In individuals already detached from the host epithelium, a central depression remained at the top of their protomerite, in the area formerly bearing the epimerite.
Keywords: kobylky; epitel; Apicomplexa; Host-Parasite Interactions; Cecum; Microscopy, Electron, Scanning; cékum; zvířata; trofozoiti; trávicí systém; mikroskopie elektronová rastrovací; Epithelium; Grasshoppers; transmisní elektronová mikroskopie; Microscopy, Electron, Transmission; Animals; interakce hostitele a parazita; Digestive System; Trophozoites